Determination of Islam in the view of Malaysia federal constitution / Abang Ikhbal Abang Bolhil ... [et al.] - Abang Bolhil, Abang Ikhbal; Yajid, Adi Aizat; Ahmad Apandi, Anas Afandi; Ahmad Apandi, Anas Afandi; Kamarudin, Ainul Hafiza (2014)
The Federal Constitution does recognise the position of religion in the country. Citizens have been guaranteed with the right to profess and practice the religion of choice in this country. The position of religions in this country is equal, with a special position given to Islam, which it is acknowledged as the religion of the federation. Under the concept of separation of power between the federal and states government, the matters relating to Islam are placed under the control of the state government. On top of that, separation of powers also occurred between the courts whereby the Syariah courts are granted judicial right to hear matters relating to Islam. Though separation of powers is enforced, there are no structured policies available in determining the status of Islam for the citizen of Malaysia. However, it has to be noted that there are few decisions made by the court pertaining to the matter.